ANALISIS PENERAPAN PERHITUNGAN DAN PEMOTONGAN PAJAK PENGHASILAN PASAL 21 RUMAH SAKIT PANCARAN KASIH MANADO - Rondonuwu, Chris Waraney; Elim, Inggriani; Pinatik, Sherly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
According to the tax regulation article 36, 2008 mentioned that everyone who fulfill the criteria to be borne of tax has the obligation to pay the income tax. The several of the employee work and the wage system can cause complicate in the implement of accountancy for the income tax.  Besides that, the company in calculating the tax can be different with the calculation as tax regulation. If the calculation from the company lower than that the regulation then the tax office will fine the company. This study aims to determine of calculating and deducting of Income Tax Articles 21 for permanent employees that implemented at Pancaran Kasih Hospital in Manado, has appropriated to the tax regulation, so it can minimalize error implementation that might happen in the future. This study uses method of quantitative description by collecting company data, observation and interview also testing data which are comparing company calculation result with writer result. Data that have been collected are: Salary payment of permanent employees list and the calculation and deduction of Income Tax article 21 list at Pancaran Kasih Hospital Manado for the year of 2016. The result shown,  that the implementation of calculation and deduction of Income Tax articles 21 for permanent employees  didn’t in line yet with the Tax Regulation article 36, 2008 and PMK no. 101/PMK.010/2016.Keywords: Income Tax article 21, Tax Regulation, Permanent Employees.